Vector Potential of a Strongly Inductive Impedance Media (Global Journal of Science Frontier Research, 2018)
Introduced the concept of a strongly inductive impedance media. Vector potential such media expressed in the wave zone as Sommerfeld integrals. This integral is calculated for strongly inductive media, which implies the existence of surface electromagnetic wave. Electrical properties of double-layer strongly inductive media described one size-listed surface impedance. Article vector potential in free space and in underlying media expressed through impedance. It is shown that an electromagnetic wave is exponentially fades in free space and in the bottom layer, and live freely distributed the first dielectric layer. Therefore it is called surface electromagnetic wave. The impedance values for some areas strongly inductive Earth surface.
Keywords: vector potential; sommerfeld integral; strongly inductive impedance media